Pipe Si Pemenggal Kepala: Sebuah Tinjauan Kritis - Esther Rita Embram (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
”Pipe Si Pemenggal Kepala” is the true story of Citak ethnic in the hinterland of Papua, which was presented as a novel. The structure of literature such as theme,    figure, characterization and background are built as a fiction to the Pipe narrative. This paper is a review criticism of the Pipe’s story, that use analytical descriptive method, by literature study. The problem are how the tracks of Primitive civilization of the Citak ethnic are still survive and continue in this modern era, and  about the struggle of the writer in creating Pipe prose that  was taken from the true story of the Papua hinterland.